The Auschwitz escape [compact disc, unabridged] - Rosenberg, Joel C., 1967- (Brilliance Audio, 2014)
A terrible darkness has fallen upon Jacob Weisz's beloved Germany. The Nazi regime, under the leadership of Adolf Hitler, has surged to power and now hold Germany by the throat. All non-Aryans, especially Jews like Jacob and his family, are treated like dogs. When tragedy strikes during one terrible night of violence, Jacob flees and joins rebel forces working to undermine the regime. But after a raid goes horribly wrong, Jacob finds himself in a living nightmare.